Systemic sclerosis in two generations family: a mother and offspring - Nilasari, D; Hamijoyo, Laniyati; Kasjmir, Yoga I; Setiyohadi, Bambang (Indonesian Journal of Rheumatology, 2009)
Systemic sclerosis (SSc) is uncommon connective tissue disease characterized by a pathological thickening and tethering of the skin and involvement of internal organ (i.e gastrointestinal tract, heart, lungs, and kidneys). Systemic sclerosis seems to result from a multifactorial process (alteration of the immune system, genetic, andÂ  environmental factors) but its pathogenesis remains unclear. A familial history of SSc represents an important risk factor for developing the disease.1 We describe two generations family who developed SSc.